Larval diapause termination in the bamboo borer, Omphisa fuscidentalis - Suphawan Suang (2018)
© 2017 Suang et al.This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. In insects, juvenile hormone (JH) and 20-hydroxyecdysone (20E) regulate larval growth and molting. However, little is known about how this cooperative control is terminating larval diapause especially in the bamboo borer, Omphisa fuscidentalis. In both in vivo and in vitro experiments, we here measured the expression levels of genes which were affected by juvenile hormone analogue (JHA: S-methoprene) and 20-hydroxyecdysone (20E) in dia-pausing O. fuscidentalis larvae. Corresponding mRNA expression changes in the subeso-phageal ganglion (SG) and prothoracic gland (PG) were evaluated using qRT-PCR. The data showed similar response patterns of JH receptor gene (OfMet), diapause hormone gene (OfDH-PBAN), ecdysone receptor genes (OfEcR-A and OfEcR-B1) and ecdysone inducible genes (OfBr-C, OfE75A, OfE75B, OfE75C and OfHR3). JHA induced the expressions of OfMet and OfDH-PBAN in both SG and PG, whereas ecdysone receptor genes and ecdysone inducible genes were induced by JHA only in PG. For 20E treatment group, expressions of ecdysone receptor genes and ecdysone inducible genes in both SG and PG were increased by 20E injection. In addition, the in vitro experiments showed that OfMet and OfDH-PBAN were up-regulated by JHA alone, but ecdysone receptor genes and ecdysone inducible genes were up-regulated by JHA and 20E. However, OfMet and OfDH-PBAN in the SG was expressed faster than OfMet and OfDH-PBAN in the PG and the expression of ecdysone receptor genes and ecdysone inducible genes induced by JHA was much later than observed for 20E. These results indicate that JHA might stimulate the PG indirectly via factors (OfMet and OfDH-PBAN) in the SG, which might be a regulatory mechanism for larval diapause termination in O. fuscidentalis.